Comparative efficacy of autologous iliac bone versus allogeneic demineralized bone matrix in lateral lumbar interbody fusion using a novel minimally invasive iliac bone retrieval tool: a self-controlled study - Jiaqi Li; Shaorong Li; Shuowen Zhang; Lin Liu; Weijian Wang; Han Wu; Qiang Yang; Wei Zhang (Journal of Orthopaedic Surgery and Research)
Abstract Objective This self-controlled study evaluates the fusion efficacy of autologous iliac bone harvested via a novel minimally invasive tool versus allogeneic demineralized bone matrix (DBM) in lateral lumbar interbody fusion (LLIF), while assessing the safety profile of the retrieval tool. Methods This study was a prospective clinical controlled study. Patients’ basic information was recorded, including the age, gender, body mass index and etc. Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) were used to evaluate clinical efficacy. Three parameters were measured, including intervertebral space height, intervertebral foraminal height and lumbar lordosis angle, before surgery and 3 days/24 months after surgery. Postoperative CT scan was used to compare the difference in interbody fusion between autologous iliac bone and allogeneic bone DBM at 6 and 24 months after surgery. Results 30 patients followed up for more than 24 months were included. The preoperative VAS for lower back and leg pain was 5.00 ± 0.87, and the preoperative ODI was 48.37 ± 8.53. The VAS for lower back and leg pain was 0.87 ± 0.63, and the ODI was 12.30 ± 2.58 at 24 months after surgery. The VAS and ODI in each postoperative stage were significantly improved compared to the preoperative (P < 0.05). The VAS of the bone extraction area was 1 (0,2) after surgery, and the pain disappeared approximately 2 days after surgery. At 6 months postoperatively, the fusion rate was 66.7% (20/30) for autologous iliac bone versus 30.0% (9/30) for allogeneic DBM (P < 0.05). the fusion rate on the autogenous iliac bone side (96.7%) was significantly higher than that on the DBM side (70.0%) at 24 months after surgery (P < 0.05). Conclusions The novel retrieval tool enables safe, minimally invasive harvest of autologous iliac bone, which achieved significantly higher fusion rates than allogeneic DBM in LLIF.